Part-Time Entrepreneurship and Risk Tolerance - Petrova, Kameliia (Journal of Applied Business and Economics, 2018)
This paper looks at the relationship between part-time entrepreneurship and risk tolerance. Part-time entrepreneurs split their time between entrepreneurial ventures and wage employment. I offer a simple model of entrepreneurial entry where individuals choose part-time, instead of full-time, entrepreneurship because they want to gain basic experience. This might be product, industry or market experience; or one related to individual-specific characteristics. People with a lower level of risk tolerance will need to first spend time acquiring this experience, and hence opting for an initial part-time involvement, before growing a full-size business. Empirical tests of the model implications are included.